DENTAL ASSISTANTS IN THE TEAMWORK - Krassimira Yaneva-Ribagina; Cvetelina Antonova (Peytchinski Publishing, 2021)
Purpose: The aim of the study was to establish the socio-demographic and professional characteristics of the sample of dental assistants and their contributions to the efficiency of dental teamwork. Material and methods: An anonymous inquiry was conducted among 108 dental assistants working in dental offices in 4 Bulgarian cities. The questionnaire consisted of 18 questions about socio-demographic and professional characteristics of the sample and their opinion about obligations, positives and negatives in the workplace, and efficiency of teamwork. The methods used in the survey were sociological (poll) and statistical (alternative analysis). Results: The socio-demographic and professional characteristics of the surveyed dental assistants were established, such as: gender and age distribution, work in active working age/pension, types of working places, location of practices, types of education and number of dentists working with over the period of their work experience. All respondents reported that they assisted the physicians in the treatment process and the majorityf them (70.37- 85.19%) cleaned, disinfected and sterilized the instruments, the workplace and the premises of the practice. Only 4.6% dealt financialelations with the patients and worked directly in their mouths. The opinion of the respondents for building a well-functioning dental team was that both the personal and professional qualities of the team members were essential. Conclusions: Dental assistants were convinced of the benefits of their assistance; between 79.6% and 58.3% of them believed that they had contributed for quicker and better job of the doctor and to patient'somfort.